Permanent record - Snowden, Edward (New York Henry Holt and Company, 2019)
"In 2013, twenty-nine-year-old Edward Snowden shocked the world when he broke with the American intelligence establishment and revealed that the United States government was secretly pursuing the means to collect every single phone call, text message, and email. The result would be an unprecedented system of mass surveillance with the ability to pry into the private lives of every person on earth. Six years later, Snowden reveals for the very first time how he helped to build this system and why he was moved to expose it. Spanning the bucolic Beltway suburbs of his childhood and the clandestine CIA and NSA postings of his adulthood, Permanent Record is the extraordinary account of a bright young man who grew up online-a man who became a spy, a whistleblower, and, in exile, the Internet's conscience
Keywords: Snowden